Tumour Treating Fields in combination with pemetrexed and cisplatin or carboplatin as first-line treatment for unresectable malignant pleural mesothelioma (STELLAR): a multicentre, single-arm phase 2 trial. Issue 12 (December 2019) - Ceresoli, Giovanni L; Aerts, Joachim G; Dziadziuszko, Rafal; Ramlau, Rodryg; Cedres, Susana; van Meerbeeck, Jan P; Mencoboni, Manlio; Planchard, David; Chella, Antonio; Crinò, Lucio; Krzakowski, Maciej; Rüssel, Jörn; et al.
Summary: Background: Tumour Treating Fields (TTFields) are a regional, antimitotic treatment for solid tumours, which is based on the delivery of low-intensity alternating electric fields. The aim of the STELLAR study was to test the activity of TTFields delivered to the thorax in combination with systemic chemotherapy for the front-line treatment of patients with unresectable malignant pleural mesothelioma. Methods: STELLAR was a prospective, single-arm, phase 2 trial done at 12 European academic and non-academic sites (five in Italy, three in Poland, one in France, one in Belgium, one in Spain, and one in the Netherlands) for treatment-naive patients with histologically confirmed unresectable malignant pleural mesothelioma. Patients were aged at least 18 years, had an Eastern Cooperative Oncology Group performance status of 0–1, and at least one measurable or evaluable lesion according to modified Response Evaluation Criteria in Solid Tumors for mesothelioma. Patients received continuous TTFields at a frequency of 150 kHz to the thorax and concomitant chemotherapy with intravenous pemetrexed (500 mg/m 2 on day 1) plus intravenous platinum (either cisplatin 75 mg/m 2 on day 1 or carboplatin area under the curve 5 on day 1) every 21 days for up to six cycles. Patients not progressing after completion of chemotherapy received TTFields as maintenance treatment until progression, patient or physician decision, or unacceptable toxic effects. The primary endpoint of the trial was overall survival. Survival analyses were done in the intention-to-treat population, and safety analyses were done in all patients who received at least 1 day of TTFields treatment. This trial is registered with ClinicalTrials.gov, NCT02397928 . Findings: Between Feb 9, 2015 and March 21, 2017, 80 patients were enrolled in the study. Median follow-up was 12·5 months (IQR 7·4–16·6). Median overall survival was 18·2 months (95% CI 12·1–25·8). The most common grade 3 or worse adverse events were anaemia (nine [11%] patients), neutropenia (seven [9%]), and thrombocytopenia (four [5%]). Skin reaction was the only adverse event associated with TTFields and was reported as grade 1–2 in 53 (66%) patients, and as grade 3 in four (5%) patients. No treatment-related deaths were observed. Interpretation: The trial showed encouraging overall survival results, with no increase in systemic toxicity. TTFields (150 kHz) delivered to the thorax concomitant with pemetrexed and platinum was an active and safe combination for front-line treatment of unresectable malignant pleural mesothelioma. Further investigation in a randomised trial is warranted. Funding: Novocure.